Obtaining Rabies Virus Purified Antigen - Nadyrova, Alsu I. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: Currently, in connection with the deterioration of the epizootic situation of rabies in the world, the question of improving the means of routine laboratory diagnostics of rabies remains highly controversial to obtain results of a high degree of reliability. Especially in demand diagnostic rapid test systems based on enzyme-linked immunosorbent assay (ELISA) and immunofluorescence (IFA) methods, the sensitivity and specificity of which depend on the degree of purification of antigenic components. Materials and Methods: In this article, a method is given for obtaining a rabies antigen and the results of an experimental study of the activity of its highly purified fractions were obtained by separation in a stepwise gradient of sucrose (20–60%) by ultracentrifugation at 30,000 g. Results: The study of electrophoretic profiles of antigenic fractions in 12.5% polyacrylamide gel showed that the major polypeptide fractions are located in the range of 44.6–70.0 kDa. According to the results of the tests in ELISA and IFA, Fraction 1 was the most active. We optimized the conditions for the formulation of the reactions, and the o-ptimal working concentrations were determined. Conclusion: The revealed immunochemical characteristics of this fraction will allow using it not only as an antigenic component for diagnostic test systems but also as an immunizing material for obtaining highly specific rabies immunoglobulins.